ANALISIS RASIO AKTIVITAS PT. FRESMON PASIFIC PRIMA PERIODE 2014-2016 - Pebriyanti1, - Anita (EKONOMIA, 2019)
PT. Fresmon Pasific Prima in fact having difficulties in managing unstable finance causes a drop in oil in PT. Fresmon Pasific Prima this prime decreases. This study aims to determine the improment in terms of the ratio of activity consisting of total assets turnover, working capital turnover, dan fixed assets turnover from 2014 to 2016.The theory of this research is financial management which focuses on the analysis of financial statement using one ratio, namely the activity ratio. The ratio is taken 3 variabels total assets turnover, working capital turnover, dan fixed assets turnover.The analytical tool used is the ratio of activity consisting of total assets turnover, working capital turnover, dan fixed assets turnover. Research data needed is 3 years, namely 2014, 2015, and 2016.The results of the study show : 1) total assets turnover decreased in 2014 to 2016. 2) working capital turnover decreased in 2014 to 2016. 3) ixed assets turnover decreased in 2014 to 2016.